Physician Perceptions of the Electronic Problem List in Pediatric Trauma Care - Hose, Bat-Zion; Hoonakker, Peter L. T.; Wooldridge, Abigail R.; Brazelton III, Thomas B.; Dean, Shannon M.; Eithun, Ben; Fackler, James C.; Gurses, Ayse P.; Kelly, Michelle M.; Kohler, Jonathan E.; McGeorge, Nicolette M.; Ross, Joshua C.; Rusy, Deborah A.; Carayon, Pascale (Applied Clinical Informatics, 2019)
Objective To describe physician perceptions of the potential goals, characteristics, and content of the electronic problem list (PL) in pediatric trauma.Methods We conducted 12 semistructured interviews with physicians involved in the pediatric trauma care process, including residents, fellows, and attendings from four services: emergency medicine, surgery, anesthesia, and pediatric critical care. Using qualitative content analysis, we identified PL goals, characteristics, and patient-related information from these interviews and the hospital's PL etiquette document of guideline.Results We identified five goals of the PL (to document the patient's problems, to make sense of the patient's problems, to make decisions about the care plan, to know who is involved in the patient's care, and to communicate with others), seven characteristics of the PL (completeness, efficiency, accessibility, multiple users, organized, created before arrival, and representing uncertainty), and 22 patient-related information elements (e.g., injuries, vitals). Physicians' suggested criteria for a PL varied across services with respect to goals, characteristics, and patient-related information.Conclusion Physicians involved in pediatric trauma care described the electronic PL as ideally more than a list of a patient's medical diagnoses and injuries. The information elements mentioned are typically found in other parts of the patient's electronic record besides the PL, such as past medical history and labs. Future work is needed to evaluate the optimal design of the PL so that users with emergent cases, such as pediatric trauma, have access to key information related to the patient's immediate problems.
Keywords: problem-oriented model; patient safety; human factors engineering; pediatric trauma; care coordination